Pengaruh Model Cooperative Learning Tipe Teams Games Tournaments (TGT) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Di Kelas IV SDN Gugus X kota Bengkulu - Sri Dadi; Victoria Karjiyati; Septi Nurlaila (JURIDIKDAS, 2018)
This study aims to determine the effect of cooperative learning model type Teams Games Tournaments (TGT) on student learning outcomes in social studies subjects in class IV SDN group X city Bengkulu. This type of research is quantitative, using the experimental method, with the design of The Pretest-Posttest Control Group Design Pretest. The research instrument used is multiple choice test sheet. Taking the test twice before and after giving treatment to the sample class. Subjects in this study were the fourth graders of SDN 58 Kota Bengkulu and fourth grade students of SDN 15 Kota Bengkulu. Result of t-test got tcount 6,079> t table 1,995. The value of t arithmetic obtained higher than the value of t table it can be concluded that there is a significant influence model of cooperative learning type teams games tournaments (TGT) on student learning outcomes in the subjects of social studies in class IV SDN group X kota Bengkulu.